School Start Times, Delinquency, and Substance Use: A Criminological Perspective - Semenza, Daniel C. (Crime & delinquency, 2020)
Research finds a lack of sleep during adolescence is associated with a variety of negative outcomes and suggests that early school start times contribute to this problem. Criminologists have largely overlooked the relevance of school start times for adolescent delinquency and substance use, precluding multidisciplinary collaborations between criminologists and other social and health scientists that might further elucidate emerging policy initiatives. We provide a theoretically informed criminological perspective explicating the mechanisms through which delaying school start times may reduce delinquency and substance use. Two pathways are proposed: one focused on self-control and another on unstructured socializing with peers. After discussing evidence supporting the pathways, this article outlines a research agenda for criminologists to contribute to understudied portions of the model.